NLP Essentials: A Practical Guide for Data Science Professionals - Thatte, Bhakti; Amarnath, K.N. (Indian Journal of Computer Science, 2024)
Natural Language Processing (NLP) is the process of extracting knowledge and information from natural language. It is a field of Computer Science, Artificial Intelligence, and linguistics concerned with the interaction between computers and human language. The basic goal of NLP is to enable people to communicate with computer in a language that they use in their everyday life. The present paper gives the ease of understanding and learning for beginners in NLP with practical knowledge along with the code base. The methodology used for understanding NLP basic building blocks is to explain every concept and demonstrate it practically through Python Code. By the virtue of the way a language is, humans comprehend it easily, but for machines to replicate it, it is a challenging problem. The present paper concentrates on making on basic building blocks of NLP with NLTK and SPACY library.